Dignity‐related existential distress in end‐of‐life cancer patients: Prevalence, underlying factors, and associated coping strategies. Issue 11 (24th September 2018) - Bovero, Andrea; Sedghi, Nader Alessandro; Opezzo, Marta; Botto, Rossana; Pinto, Manuela; Ieraci, Valentina; Torta, Riccardo
Abstract: Objective: Cancer patients often have to face increasing levels of existential distress (ED) during disease progression, especially when nearing death. This cross‐sectional study aimed to assess the prevalence of the dignity‐related existential distress (DR‐ED) in a sample of end‐of‐life cancer patients, and to explore the "existential distress" Patient Dignity Inventory (PDI‐IT) subscale internal structure and its associations with different coping strategies. Methods: Two hundred seven cancer inpatients with a Karnofsky Performance Status ≤50 and a life expectancy of 4 months or less have been examined with the following self‐report measures: PDI‐IT, Demoralization Scale (DS‐IT) and Brief Coping Orientation to Problem Experienced (Brief‐COPE). The existential distress PDI‐IT subscale factor structure was explored through principal component analysis, and the DR‐ED associations with the other considered variables were examined through X 2 tests, MANOVA, and multivariate regression analysis. Results: Dignity‐related existential distress was a problem/major problem for 18.8% of the patients, especially for the younger ( F (1, 205) = 3.40; P = 0.020) and more demoralized ( F (1, 205) = 20.36; P < 0.001) individuals. Factor analysis supported 2 dimensions labeled "self‐discontinuity" and "loss of personal autonomy, " accounting for 58% of the variance. Positive reframing ( β = −0.146, P < 0.05) and self‐blame ( β = 0.247, P < 0.001) coping styles emerged as DR‐ED significant predictors. Conclusions: This study showed how DR‐ED is a relevant problem for patients nearing death and furthermore highlighted 2 underlying factors. Finally, the research has shown that positive reframing and self‐blame coping styles might be clinically relevant elements for interventions on ED.